Veranderende perspektiewe op seksualiteit en die huwelik in "n postmoderne kerk - Botha, Annelie (HTS teologiese studies, 2013)
Shifting ecclesial perspectives on sexuality and marriage in a postmodern world. The aim of the article is to critically question whether the church is still able to guide people to make meaningful choices with regard to marriage and sexuality when values keep shifting. This question is especially relevant where the church still tends to uphold premodern values (heteronormative, patriarchal, monogamous) with regard to sexuality and marriage as the only (prescriptive) model for marriage in a postmodern world. The article consists of the following sections: changing values versus traditional values; marriage and sexuality from biblical times to the present; church in crisis; and eco-feminist family ethics.